Photoresponsive Piezoelectrics - Bai, Yang (Frontiers in Materials, 2021)
Most piezoelectric materials are not interactive with visible light, meaning that their band gaps are beyond the photon energies of the visible part of the light spectrum. The first narrow band gap (1.1 eV, the same as silicon) ferroelectric material based on the oxide perovskite structure has been achieved by doping Ni on the B-sites of KNbO3 and paring the Ni2+ ions with oxygen vacancies to form defect dipoles to ease the band-band transition. This band gap engineered ferroelectric material has also been proved to be piezoelectric. The Ni-doping strategy for band gap engineering has been successfully applied to other perovskite compositions. As a result, several materials with simultaneously good piezoelectricity and a visible-range band gap have been developed. Such photoresponsive piezoelectrics have potential applications in opto-electrical dual-source actuators, single-material multi-sensors and multi-source energy harvesters. This mini review focuses on the works of simultaneous tuning of piezoelectricity and band gap, which have not previously been discussed as an individual topic in existing reviews. Pioneer works on the applications of photoresponsive piezoelectrics are also presented. Since most of such materials are built on the frame of lead-free perovskite oxides, their band gap (without degrading the piezoelectricity) provides an additional benefit to environmentally friendly lead-free piezoelectrics (compared to lead-based counterparts such as PZT [Pb(Zr,Ti)O3)]. This review aims to draw the attention of piezoelectric scientists and device engineers, so that potential applications of photoresponsive piezoelectrics can be comprehensively investigated, as well as more material options that can be offered in future works.